DNA annealing by Rad52 Protein is stimulated by specific interaction with the complex of replication protein A and single-stranded DNA - Sugiyama, Tomohiko (The National Academy of Sciences, 1998)
Homologous recombination in Saccharomyces cerevisiae depends critically on RAD52 function. In vitro, Rad52 protein preferentially binds single-stranded DNA (ssDNA), mediates annealing of complementary ssDNA, and stimulates Rad51 protein-mediated DNA strand exchange. Replication protein A (RPA) is a ssDNA-binding protein that is also crucial to the recombination process. Herein we report that Rad52 protein effects the annealing of RPA–ssDNA complexes, complexes that are otherwise unable to anneal. The ability of Rad52 protein to promote annealing depends on both the type of ssDNA substrate and ssDNA binding protein. RPA allows, but slows, Rad52 protein-mediated annealing of oligonucleotides. In contrast, RPA is almost essential for annealing of longer plasmid-sized DNA but has little effect on the annealing of poly(dT) and poly(dA), which are relatively long DNA molecules free of secondary structure. These results suggest that one role of RPA in Rad52 protein-mediated annealing is the elimination of DNA secondary structure. However, neither Escherichia coli ssDNA binding protein nor human RPA can substitute in this reaction, indicating that RPA has a second role in this process, a role that requires specific RPA–Rad52 protein interactions. This idea is confirmed by the finding that RPA, which is complexed with nonhomologous ssDNA, inhibits annealing but the human RPA–ssDNA complex does not. Finally, we present a model for the early steps of the repair of double-strand DNA breaks in yeast.